SURFACE CHEMISTRY AND RELATIVE NI SORPTIVE CAPACITIES OF SYNTHETIC HYDROUS MN OXYHYDROXIDES UNDER VARIABLE WETTING AND DRYING REGIMES - Kennedy C.; Smith D.S.; Warren L.A. (My University, 2004)
The surface binding site characteristics and Ni sorptive capacities of synthesized hydrous Mn oxyhydroxides experimentally conditioned to represent three hydrological conditions-MnOXW, freshly precipitated; MnOXD, dried at 37°C for 8 d; and MnOXC, cyclically hydrated and dehydrated (at 37°C) over a 24-h cycle for 7 d-were examined through particle size analysis, surface acid-base titrations and subsequent modelling of the pKa spectrum, and batch Ni sorption experiments at two pH values (2 and 5). Mineralogical bulk analyses by XRD indicate that all three treatments resulted in amorphous Mn oxyhydroxides; i.e., no substantial bulk crystalline phases were produced through drying. However, drying and repeated wetting and drying resulted in a non-reversible decrease in particle size. In contrast, total proton binding capacities determined by acid-base titrations were reversibly altered with drying and cyclically re-wetting and drying from 82 +/- 5 μmol/m2 for the MnOXW to 21 +/- 1 μmol/m2 for the MnOXD and 37 +/- 5 μmol/m2 for the MnOXC. Total proton binding sites measured decreased by ~75% with drying from the MnOXW and then increased to ~50% of the MnOXW value in the MnOXC. Thus, despite a trend of higher surface area for the MnOXD, a lower total number of sites was observed, suggesting a coordinational change in the hydroxyl sites. Surface site characterization identified that changes also occurred in the types and densities of surface sites for each hydrologically conditioned Mn oxyhydroxide treatment (pH titration range of 2-10). Drying decreased the total number of sites as well as shifted the remaining sites to more acidic pKa values. Experimentally determined apparent pHzpc values decreased with drying, from 6.82 +/- 0.06 for the MnOXW to 3.2 +/- 0.3 for the MnOXD and increased again with rewetting to 5.05 +/- 0.05 for the MnOXC. Higher Ni sorption was observed at pH 5 for all three Mn oxyhydroxide treatments compared to pH 2. However, changes in relative sorptive capacities among the three treatments were observed for pH 2 that are not explainable simply as a function of total binding site density or apparent pHzpc values. These results are the first to our knowledge, to quantitatively link the changes induced by hydrologic variability for surface acid base characteristics and metal sorption patterns. Further, these results likely extend to other amorphous minerals, such as Fe oxyhydroxides, which are commonly important geochemical solids for metal scavenging in natural environments.